Evaluation of an education program upon women's knowledge toward management of Breast Self – Examination(BSE) (Baghdad Science Journal, 2025)
To determine the evaluation of education program on women's knowledge regarding managing BSE. The present quasi- experimental study, Non-probability (purposive), sample consisting of (260) women who are employee, and students in both colleges (Nursing college, Medical and Health Techniques College). The sample consist of two groups, study group (130) including those in (Nursing college), and control group (130) in (Medical and Health Techniques College). A questionnaire was constructed which included, Demographic information, Reproductive information, Family history, Previous medical history, and information about women's knowledge toward management of breast self examination (BSE). Instrument validity and reliability was determined. Data were collected through the use of the questionnaire, the application of the educational program a post-test was done for the study only which use the lectures, booklets, training practice of BSE, and video film. Analysis of data was performed through the application of descriptive and inferential statistical data analysis approach.Revealed that the women in the study group had benefited from the implementation of the educational program; their knowledge regarding managing BSE was adequately improved and developed. The study illustrated significant difference between women's knowledge means in pre and post test periods regarding their managing for BSE. Implementation of proposed model of continuous medical education for women for BSE within the scope of their work.